1981
DOI: 10.1111/j.1365-2230.1981.tb02308.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of psoriasis on the sufferer

Abstract: Summary Questions from patients suffering from psoriasis indicate that treatment is carried out with diligence, but embarrassment still inhibits daily activities and the choice of clothing. The establishment of Day Care Centres, discussion groups and The Psoriasis Association may help to overcome this embarrassment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 5 publications
2
26
0
Order By: Relevance
“…Although most authors also did not find any difference in the level of stigmatization between genders (9,24,25), Ginsburg & Link (11) noticed that women experienced greater distress due to psoriasis and were more sensitive to stigmatization than their male counterparts. In addition, Perrot et al (26) reported that women experienced guilt and shame significantly more severely than men.…”
Section: Discussionmentioning
confidence: 95%
“…Although most authors also did not find any difference in the level of stigmatization between genders (9,24,25), Ginsburg & Link (11) noticed that women experienced greater distress due to psoriasis and were more sensitive to stigmatization than their male counterparts. In addition, Perrot et al (26) reported that women experienced guilt and shame significantly more severely than men.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have looked at selected groups in whom the disability might be expected to be worse 3 4 5 13 14. Nevertheless, even in those selected groups doctors underestimate the degree of disability caused by psoriasis 3 4.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have shown that doctors probably underestimate the degree of psychological and social morbidity 3 4…”
Section: Introductionmentioning
confidence: 99%
“…Theories about marking and stigma were chosen, as one of the most serious side effects of living with psoriasis is the visibility of the disease (Jobling, 1976;Stankler, 1981). Our previous studies raised the question of visibility as a troublesome matter for the patient (Uttjek et al, 2004(Uttjek et al, , 2005.…”
Section: Theoretical Frame Of Referencementioning
confidence: 99%